The influence on coagulation of transdermal estrogen hormone replacement therapy as a preoperative preparation of the tissue before vaginal hysterectomy - Antovska, Vesna; Dimitrov, Goran; Jovanovska, Viktorija; Subeska-Stratrova, Slavica; Kiprovska, Gordana; Livrinova, Vesna (Macedonian Academy of Sciences and Arts, 2004)
In 32 postmenopausal patients who underwent vaginal hysterectomy due to the presence of uterine prolapse at the Department of Uro-gynaecology and Pelvic Floor Disorders in the Clinic of Gynaecology and Obstetrics, Medical School, Skopje in the period from 1st January 2002 to 1st January 2003, and who were preoperatively treated with transdermal estradiol 50 microg/day during 14 days the following parameters of the coagulating status were estimated: prothrombin time (PT) that is expressed in: absolute value, percentage and INR; activated partial thromboplastin time (aPTT Pathrombin SL); thrombin time and platelets number before and after hormone replacement therapy. After 14-day transdermal estrogen therapy, the parameters: PT, PT%, PT INR, aPTT Pathrombin SL didn't expressed significant changes, the thrombin time expressed significant extension, and the platelets expressed a significant decrease. According to our results, the transdermal estrogens might not have any influence on the hepatic synthesis of coagulating factors till the step of prothrombin formation. They might have an essential influence on the step of prothrombin transformation into thrombin, as well as on the process of megacaryocytes segregation into platelets.